Periodontal condition, changes in salivary biochemical parameters, and oral health-related quality of life in patients with anorexia and bulimia nervosa - Chiba, Fernando Y. [UNESP]; Sumida, Doris H. [UNESP]; Moimaz, Suzely A S [UNESP]; Chaves Neto, Antônio H [UNESP]; Nakamune, Ana C M S [UNESP]; Garbin, Artênio J I [UNESP]; Garbin, Cléa A S [UNESP] (Wiley, 2019)
BACKGROUND: Anorexia and bulimia nervosa can have significant effects on oral health. Assessment of enzyme concentrations in saliva can be useful for obtaining information on molecular biomarkers for the prevention, monitoring, and diagnosis of oral diseases. This study investigated the periodontal condition, changes in salivary biochemical parameters, and oral health-related quality of life (OHRQoL) in patients with anorexia and bulimia nervosa. METHODS: The study comprised 60 women patients who attended a Brazilian medical school. Participants were divided into two groups: patients with anorexia and bulimia nervosa (ABN; n = 30) and control patients (CN; n = 30). Oral clinical examinations were carried out to evaluate the periodontal condition by Community Periodontal Index, and interviews using the Oral Health Impact Profile (OHIP-14) were conducted to assess OHRQoL. Saliva samples were collected for the evaluation of salivary concentrations of total protein, alanine aminotransferase (ALT), aspartate aminotransferase (AST), lactate dehydrogenase (LDH), and thiobarbituric acid reactive substance (TBARS), and salivary flow rate. RESULTS: Periodontal condition in the ABN group was significantly worse than that in the CN group. The ABN group showed significantly higher salivary concentrations of total protein, AST, ALT, and LDH than the CN group. There was no significant difference in the salivary concentrations of TBARS among the groups. The OHIP-14 score was higher in the ABN group than in the CN group. CONCLUSION: Anorexia and bulimia nervosa are associated with poor periodontal condition, elevated salivary concentrations of total protein, AST, ALT, and LDH, decreased salivary flow rate and a significant adverse impact on OHRQoL.
Keywords: anorexia nervosa; bulimia nervosa; periodontal diseases; quality of life; saliva